Useful Daily Behaviour to Remove Asymptomatic Bacteriuria in an Eight Years Age Girl with Spina Bifida Occulta - Taniguchi, Kazuto; Nakashima, Takema; Ichiyama, Yasunobu; Yamamoto, Hirokazu; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2018)
Asymptomatic bacteriuria is occasionally found in healthy children. However, the fact that spina bifida occulta can be hidden in asymptomatic bacteriuria is not well known. We report an 8-year-old girl with asymptomatic bacteriuria. Spina bifida occulta was revealed by radiological examinations. Simple daily behavior, consisting of keeping the genitals clean, rehydrating regularly and not prolonging urination, was useful for removing asymptomatic bacteriuria in spina bifida occulta.